Tracking Agriculture-Induced Fertility Among Yorùbá Farmers of Southwestern Nigeria - Fausat Motunrayo Ibrahim (University of Belgrade, 2020)
The dynamics of agricultural production in African peasant economies featured human fertility in no small measure. The role of increased fertility in agricultural productivity is explained by opposing ideologies, yet, African perspectives on increased fertility for agricultural production, in the current social climate, are seemingly deficient. Using a triangulation of qualitative methods, this work explores agriculture-induced fertility among Yorùbá farmers of Southwestern Nigeria. The findings clearly and dominantly indicate that the option of increasing fertility deliberately through polygyny, for improved agricultural production has tremendously diminished. Instead, concerns over optimum child development, which can hardly be guaranteed with continued agriculture-induced fertility, are stressed. This shows that Yorùbá farmers’ disposition towards increasing fertility is dictated by pecuniary circumstances, thereby accentuating the rationality of Yorùbá culture and its people.